Experimental Investigation On The Power Performance Of A Hybrid Turbine Blade For Hydrokinetic Application - Zamri, Siti Nuruljannah Mohamad (Universiti Sains Malaysia, 2021)
Hydrokinetic turbines which are similar in design and working principle to wind turbines, are typically categorized into two types; axial flow turbines and cross-flow turbines. The cross-flow turbine is commonly used in low-flow rivers and streams. The environment set for the turbine designed in this project is a river with a low-flow velocity, and hence, the cross-flow hydrokinetic turbine is used in this study that focuses on a Savonius and Darrieus turbine. The Savonius turbine is a drag-based rotor and the Darrieus turbine is a lift-based rotor. The Darrieus turbine has a higher power coefficient when compared to the Savonius turbine. However, the Darrieus turbine has a problem with self-starting. To improve the turbine's efficiency, an experiment was conducted to investigate the power performance of the hybrid Savonius-Darrieus turbine for hydrokinetic application. An experiment with two-stages concaved Savonius turbine blades in combination with three H-Darrieus turbine blades was performed in a closed-loop wind tunnel. The range of the turbine’s tip speed ratio was set to 0.5 to 1.0 for flow velocity ranges of 7 m/s - 10.0 m/s (that represents the average velocity in low flow river or stream). The turbine was designed with a two-stages Savonius for optimal performance based on Saha et al., (2008) with an overlap ratio of 0.05. As the drag coefficient of the concave surface is greater than that of the convex side, when compared to the incoming freestream, the drag force experienced by the concave half is greater than that of the returning blade. The net torque that drives the turbine is created by the difference in drag force, and the drag force difference spins the rotor to generate mechanical power. In addition, with the overlap ratio, airflow can pass through the gap between the blades and act on the concave side of the returning blades. The proposed Darrieus turbine, on the other hand, would use a symmetrical airfoil rather than a cambered airfoil to overcome the resistive torque and begin rotating. Also, the symmetrical airfoil has the advantage of an early start and the ability to generate power at low wind speeds of 3.5 m/s. The experiment results were then compared to data from Saha et al. (2008), Kamoji et al. (2008), Golecha et al. (2011), Saini et al. (2019), Gavalda et al. (1990), Bhuyan and Biswas (2014) and Siddiqui et al. (2016). From the results, the maximum power coefficient (CP) obtained is 0.11 corresponding to a tip speed ratio (TSR) value of 0.65. Moreover, the maximum torque coefficient obtained is 0.19 corresponding to a TSR value of 0.54. The CP obtained, even though did not achieve our target for this study, it still follows the trend of the optimum power coefficient for a small turbine. Regardless of the outcome, this maximum CP can still be improved and a few modifications to the hybrid turbine are proposed for future research.